2020
DOI: 10.1097/md.0000000000020125
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transforaminal endoscopic decompression for the treatment of intraspinal tophaceous gout

Abstract: Rationale: Intraspinal tophaceous gout is relatively rare condition presenting with major clinical manifestations, such as spinal cord or nerve roots compressions (radiculopathy). It is usually difficult to differentiate intraspinal tophaceous gout, lumbar disc herniation, stenosis of spinal canal, ossification of ligamentum flavum, and other degenerative spinal disorders from each other. Patient concerns: A 64-year-old man was admitted with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It was estimated that 65.4% of patients had some kind of neurological deficit, such as loss of sensation, radiculopathy, bowel/bladder dysfunction, motor weakness or even quadriparesis ( 2 ). Owing to its diverse location in the spine and atypical clinical symptoms, the differential diagnosis includes epidural abscess, metastatic disease, spondylodiscitis, rheumatoid arthritis and other degenerative spinal disorders ( 3 , 7 ). It was also reported that ~24.6% of patients with spinal gout had no history of gout or hyperuricemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was estimated that 65.4% of patients had some kind of neurological deficit, such as loss of sensation, radiculopathy, bowel/bladder dysfunction, motor weakness or even quadriparesis ( 2 ). Owing to its diverse location in the spine and atypical clinical symptoms, the differential diagnosis includes epidural abscess, metastatic disease, spondylodiscitis, rheumatoid arthritis and other degenerative spinal disorders ( 3 , 7 ). It was also reported that ~24.6% of patients with spinal gout had no history of gout or hyperuricemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that ~24.6% of patients with spinal gout had no history of gout or hyperuricemia ( 2 ). Although relatively rare, orthopedic surgeons should take it into consideration as a differential diagnosis when the patient has chronic lower back pain, even if the patient has normal serum uric acid levels and no history of gout ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptomatic intraspinal gout is rare, and there is no consensus on its treatment to date. The majority of relevant studies have demonstrated that open laminectomy is the rst choice for selected patients, but it is often accompanied by a large incision and a spinal instability postoperation [2][3][4][5] . Recently, we rst applied percutaneous transforaminal endoscopy for intraspinal gout, and the symptoms of neurological de cits and pain were immediately relieved without complications postoperatively.…”
Section: Introductionmentioning
confidence: 99%